2015
DOI: 10.1038/srep13810
|View full text |Cite
|
Sign up to set email alerts
|

Early amplitude-integrated electroencephalography predicts brain injury and neurological outcome in very preterm infants

Abstract: Early amplitude-integrated electroencephalography (aEEG) has been widely used in term infants with brain injury to predict neurodevelopmental outcomes; however, the prognostic value of early aEEG in preterm infants is unclear. We evaluated how well early aEEG could predict brain damage and long-term neurodevelopmental outcomes in very preterm infants compared with brain imaging assessments. We found that severe aEEG abnormalities (p = 0.000) and aEEG total score < 5 (p = 0.006) within 72 h after birth were pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…If infants had blood transfusions, blood samples were collected at least 3 days after that. Head ultrasound was performed on all patients within 3 days after birth and then weekly until discharge (at least 4 sessions of ultrasonography were performed, which depended on the gestational age), and cerebral magnetic resonance imaging (MRI) was performed at 40 weeks of corrected age to determine the presence and extent of brain injury, hemorrhage, or thrombosis 26. Data regarding complications of prematurity, including ICH, PVL, bronchopulmonary dysplasia (BPD), necrotizing enterocolitis (NEC), sepsis, and ROP, were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…If infants had blood transfusions, blood samples were collected at least 3 days after that. Head ultrasound was performed on all patients within 3 days after birth and then weekly until discharge (at least 4 sessions of ultrasonography were performed, which depended on the gestational age), and cerebral magnetic resonance imaging (MRI) was performed at 40 weeks of corrected age to determine the presence and extent of brain injury, hemorrhage, or thrombosis 26. Data regarding complications of prematurity, including ICH, PVL, bronchopulmonary dysplasia (BPD), necrotizing enterocolitis (NEC), sepsis, and ROP, were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Individual metrics of electroencephalography6131415 and near-infrared spectroscopy (NIRS)1617 have been used independently to assess the function of neurovascular unit, but the ability to study coupling in real time of NIRS and EEG in HIE has received little attention11171819 These methods demonstrated that a severe asphyxia insult leads to impaired function, but the extent of dysfunctional neurovascular coupling (NVC), and its impact on clinical outcome of newborns with encephalopathy cannot be currently assessed in real time due to limited methodology2021.…”
mentioning
confidence: 99%
“…One systematic review on developmental care (10) recommended combining electroencephalography (EEG) to a measure of neurobehavioral development for assessing the effectiveness of interventions with preterm infants. Recent advances support the idea that brain activity and oxygenation during the neonatal period play a crucial role in the preservation and development of brain connections, and thus in infants' brain functioning and growth (43,44), and can predict their neurodevelopmental status in early childhood (45,46). Therefore, combined with other standardized instruments, EEG as a measure of infants' neurodevelopment could be used in future studies.…”
Section: Implications For Clinical Practicementioning
confidence: 99%